Pricklier with the proper predator? Predator‐induced small‐scale changes of spinescence in Daphnia. Issue 23 (17th November 2021) - Diel, Patricia; Rabus, Max; Laforsch, Christian
Abstract: Phenotypic plasticity in defensive traits is a common response of prey organisms to variable and unpredictable predation regimes and risks. Cladocerans of the genus Daphnia are keystone species in the food web of lentic freshwater bodies and are well known for their ability to express a large variety of inducible morphological defenses in response to invertebrate and vertebrate predator kairomones. The developed defenses render the daphnids less susceptible to predation. So far, primarily large‐scale morphological defenses, like helmets, crests, and tail‐spines, have been documented. However, less is known on whether the tiny spinules, rather inconspicuous traits which cover many Daphnia 's dorsal and ventral carapace margins, respond to predator kairomones, as well. For this reason, we investigated two Daphnia species ( D . magna and D. longicephala ) concerning their predator kairomone‐induced changes in dorsal and ventral spinules. Since these small, inconspicuous traits may only act as a defense against predatory invertebrates, with fine‐structured catching apparatuses, and not against vertebrate predators, we exposed them to both, an invertebrate ( Triops cancriformis or Notontecta maculata ) and a vertebrate predator ( Leucaspius delineatus ). Our results show that the length of these spinules as well as spinules‐covered areas vary, likely depending on the predator the prey is exposed to. We further present first indications of a Daphnia species‐specific elongation of the spinules and an increase of the spinules‐bearing areas. Although we cannot exclude that spinescence is altered because it is developmentally connected to changes in body shape in general, our results suggest that the inducible alterations to the spinule length and spinules‐covered areas disclose another level of predator‐induced changes in two common Daphnia species. The predator‐induced changes on this level together with the large‐scale and ultrastructural defensive traits may act as the overall morphological defense, adjusted to specific predator regimes in nature. Abstract : We investigated two Daphnia species ( D . magna and D. longicephala ) concerning their predator kairomone‐induced changes of the dorsal and ventral spinules. Since these small, inconspicuous traits may only act as a defense against predatory invertebrates, with fine‐structured catching apparatuses, and not against vertebrate predators, we exposed them to both, an invertebrate ( Triops cancriformis or Notontecta maculata ) and a vertebrate predator ( Leucaspius delineatus ). Our study discovers indications of predator‐dependent, alongside Daphnia clone‐specific, defensive increases in spinescence.